Měkkýši jihovýchodních údolí Prahy - Dagmar Říhová; Štěpánka Podroužková; Alena Kocurková; Magda Drvotová; Jana Škodová; Jan Oravec; Lucie Juřičková (Malacologica Bohemoslovaca)
By the standards of Prague, its south-eastern part represents a less diversified part of the city in terms of relief and geological composition. The present article describes the development of terrestrial mollusc fauna since the beginning of explorations of this area in the 1940s and a comparison with the current in-depth exploration. Currently, 82 species have been recorded here (6 bivalves, 12 aquatic snails, 64 land gastropods). Most of the mollusc fauna occur in the linear vegetation along the waterways, suitable for the ecological group of less demanding forest snails dominating the entire Prague area. Specific to this part of the city are several more sensitive forest snails, which are the relicts of certainly much more widespread forest communities in the past. The first findings of Daudebardia brevipes and the non-native species Deroceras invadens and Lucilla scintilla in the wild nature of Prague are significant.